The value relevance of Other Comprehensive Income: Extensive evidence from Europe. (12th August 2020) - Harasheh, Murad; Doni, Federica; Franceschelli, Maria Vittoria; Amaduzzi, Andrea
Abstract: This study investigates the value relevance of the Other Comprehensive Income (OCI). Limited literature has focused on the relevance on equity price and return. We go further by including the usefulness of OCI volatility on equity total risk which contributes to the inconclusive debate on how markets perceive different pieces of accounting information. After the adoption of the IAS (1), companies must disclose information about OCI, which shifts the focus from net income to comprehensive income. It shows the return that a company has made on its economic resources, determining a potential support for improving investors' decision‐making process. Contrarily, some studies demonstrated that comprehensive income is not a true performance indicator because it includes nonrecurring items (i.e., unrealized gains and losses related to the change in the fair market value of available‐for‐sales securities). To test the relevance aspects of the OCI, we focus on the European context, and in particular on the analysis of the super sector leaders in Europe, the companies of the STOXX 50 index over the period from 2010 to 2016. We find a weak negative association between OCI and equity price, and it is a firm specific effect. Similar weak mixed relationships with equity return is found and in particular it is a year‐specific effect. In addition, our findings reveal that the volatility of OCI is positively related to equity total risk. Compared to U.S and other international contexts, the findings provide novel insights at the European Union level about the inconsistent valuation usefulness of OCI.